Identification of Three Clf-Sdr Subfamily Proteins in Staphylococcus warneri, and Comparative Genomics Analysis of a Locus Encoding CWA Proteins in Staphylococcus Species - Sun, Zhewei; Zhang, Xueya; Zhou, Danying; Zhou, Kexin; Li, Qiaoling; Lin, Hailong; Lu, Wei; Liu, Hongmao; Lu, Junwan; Lin, Xi; Li, Kewei; Xu, Teng; et al. (Frontiers in Microbiology, 2021)
Coagulase-negative Staphylococcus warneri is an opportunistic pathogen that is capable of causing several infections, especially in patients with indwelling medical devices. Here, we determined the complete genome sequence of a clinical S. warneri strain isolated from the blood culture of a 1-year-old nursling patient with acute upper respiratory infection. Genome-wide phylogenetic analysis confirmed the phylogenetic relationships between S. warneri and other Staphylococcus species. Using comparative genomics, we identified three cell wall-anchored (CWA) proteins at the same locus (sdr), named SdrJ, SdrK and SdrL, on the chromosome sequences of different S. warneri strains. Structural predictions showed that SdrJ/K/L have structural features characteristic of Sdr proteins but exceptionally contained an unusual N-terminal repeat region. However, the C-terminal repetitive (R) region of SdrJ contains a significantly larger proportion of alanine (142/338, 42.01%) than the previously reported SdrI (37.00%). Investigation of the genetic organization revealed that the sdrJ/K/L genes were always followed by one or two glycosyltransferase genes, gtfA and gtfB and were present in an ~56 kb region bordered by a pair of 8 bp identical direct repeats, named Sw-Sdr. This region was further found to be located on a 160-kb region subtended by a pair of 160-bp direct repeats along with other virulence genes and resistance genes. Sw-Sdr contained a putative integrase that was probably a remnant of a functional integrase. Evidence suggests that Sw-Sdr is improbably an efficient pathogenicity island. A large-scale investigation of Staphylococcus genomes showed that sdr loci were a potential hotspot of insertion sequences (ISs), which could lead to intraspecific diversity at these loci. Our work expanded the repository of Staphylococcus Sdr proteins, and for the first time, we established the connection between sdr loci and phylogenetic relationships and compared the sdr loci in different Staphylococcus species, which provided large insights into the genetic environment of CWA genes in Staphylococcus.